PENANAMAN DAN PEMANFAATAN TANAMAN OBAT KELUARGA SEBAGAI MINUMAN IMMUNE BOOSTER - Pharmawati, M.; Wrasiati, L.P.; Wijaya, I.M.A.S.; Wiratmini, N.I. (Buletin Udayana Mengabdi; Vol 21 No 3 (2022): Buletin Udayana Mengabdi, 2022)
The immune system is important in dealing with foreign objects that enter the body. A good body defense system is very important in the existence of the corona virus disease 19 (COVID-19) pandemic caused by the SARS-CoV2. The immune system can be improved by consuming foods with balanced nutrition and various kinds of herbs, in the form of herbal medicine. Jamu is a product derived from medicinal plants that can function as an immune booster. The government has campaigned for the planting of family medicinal plants (TOGA) as an effort to maintain health. In Budaga Village, Klungkung Regency, several families have planted medicinal plants, but the types of are still limited and the processing carried out is still very simple, namely brewing the leaves or plant rhizomes. The purpose of this activity was to introduce cultivation techniques of various kinds of medicinal plants, as well as to train member of PKK of Budaga Village in processing medicinal plants into herbal jamu immune booster. The activity was held on September 1, 2021, attended by representatives of PKK in Budaga Village. The methods used are lectures, demonstrations and direct practice of seeding and planting medicinal plants and practice of preparing jamu. The results of this activity are that the community can cultivate medicinal plants and able to prepare jamu following recipe from Kementerian Kesehatan RI. This activity produced seeds of medicinal plants ginger, red ginger, Piper betle, lemongrass, turmeric, mint and three herbal products, namely jamu gula asam, kunyit asam and temulawak.   Keywords: Budaga Village, immune booster, jamu, PKK, TOGA